Uma Aventura: O estagiário de Educação Física na Escola - Bruno Miguel Nunes Moreira (2021)
This document was accomplished within the scope of the Professional Internship, included in the 2nd year of the 2nd cycle in Physical Education Teaching in Basic and Secondary Education at the College of Sports of the University of Porto. This work reports the adventure that the author had, over a year of internship, with all its difficulties and overcomings experienced. The professional internship took place at the High School of Valongo, in the school year of 2020/2021, with a class of the tenth year, from the scientific-humanistic and technological course. This exhibition results from the introspection about the performance of the intern teacher, throughout his career in the Professional Internship. The internship report is divided into seven chapters. The first chapter is reserved for a brief introduction. The second chapter presents the trainee teacher's personal framework, while in the third chapter the institutional framework is portrayed. In the fourth, fifth and sixth chapters, the operational framework is developed, in which three core areas are focused, area 1, organization and management of teaching and learning, area 2, school participation and community relations, and area 3, professional development, respectively. It is remarkable that in professional development, a research study was carried out about the students' motivation to exercise in the author's class, which revealed that there were relevant increases in the reasons for the physical exercise practice, between the deconfinement and the end of the school year. The seventh chapter is reserved for the final considerations and expectations for the future. With this document, the author discusses his decisions, difficulties and emotions felt throughout his career, which led to the construction of his professional identity: a physical education teacher.